The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1001/jamanetworkopen.2019.20476
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Posttraumatic Stress Disorder and Mortality Among Responders and Civilians Following the September 11, 2001, Disaster

Abstract: IMPORTANCE Posttraumatic stress disorder (PTSD) has been associated with increased mortality, primarily in studies of veterans. The World Trade Center Health Registry (Registry) provides a unique opportunity to study the association between PTSD and mortality among a population exposed to the World Trade Center attacks in New York, New York, on September 11, 2001 (9/11). OBJECTIVES To assess whether 9/11-related probable PTSD (PTSD) is associated with increased mortality risk, as well as whether this associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 72 publications
1
45
0
Order By: Relevance
“…Studies that examine the impact of the clinical environment on clinician stress levels during the COVID-19 pandemic are just emerging [ 9 ]. Negative implications of burnout prior to the current pandemic include increased risk of chronic physiological conditions (e.g., cardiovascular disease; obesity) [ [10] , [11] , [12] ], psychiatric conditions (e.g., depression, post-traumatic stress disorder [PTSD], and suicidal thoughts) [ [12] , [13] , [14] ], and adverse organizational outcomes (e.g., low workforce retention rates; poorer quality of care) [ 15 , 16 ]. Stress, a precursor to burnout, may be exacerbated by specific work environment factors, [ 17 ] home characteristics, [ 18 , 19 ] and pre-existing chronic health conditions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examine the impact of the clinical environment on clinician stress levels during the COVID-19 pandemic are just emerging [ 9 ]. Negative implications of burnout prior to the current pandemic include increased risk of chronic physiological conditions (e.g., cardiovascular disease; obesity) [ [10] , [11] , [12] ], psychiatric conditions (e.g., depression, post-traumatic stress disorder [PTSD], and suicidal thoughts) [ [12] , [13] , [14] ], and adverse organizational outcomes (e.g., low workforce retention rates; poorer quality of care) [ 15 , 16 ]. Stress, a precursor to burnout, may be exacerbated by specific work environment factors, [ 17 ] home characteristics, [ 18 , 19 ] and pre-existing chronic health conditions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Giesinger et al3 reveal the importance of measuring PTSD symptoms longitudinally. While the study is important and the analyses are robust, future WTC Health Registry research could model the association between PCL improvement and mortality.…”
mentioning
confidence: 97%
“…including 487 with cardiovascular mortality and 230 with an external cause of death (including suicide and accidental poisoning). The study by Giesinger et al 3 was unique in that it compared the magnitude of the association between PTSD and mortality using 2 separate survival modeling approaches. First, PTSD was modeled as present or absent at baseline, and second, PTSD was treated as a time-varying exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequently studied health outcomes linked to 9/11 include physical health conditions such as asthma, autoimmune diseases, cardiovascular diseases, and cancer, 1–6 mental health conditions such as posttraumatic stress disorder (PTSD) and depression, 7–10 and physical and mental health comorbidities 11 . Many studies have reported significant associations between these health outcomes and 9/11‐related dust exposure, 1–6 with some studies also noting the temporal associations between mental health problems, particularly 9/11‐related PTSD, and physical health outcomes 12–17 …”
Section: Introductionmentioning
confidence: 99%